2015
DOI: 10.1253/circj.cj-15-0366
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Ultrasound Promotes Reperfusion and Angiogenesis in a Rat Model of Peripheral Arterial Disease

Abstract: Circulation Journal Official Journal of the Japanese Circulation Society http://www. j-circ.or.jpNishida et al demonstrated the potential of SWT as a treatment for IHD; in a porcine model of chronic IHD, SWT improved ejection fraction, wall thickening, myocardial blood flow and capillary density compared with sham therapy. 5 Similar results were demonstrated in porcine models of acute myocardial infarction 6 and ischemia-reperfusion injury. 7 Human studies soon followed, with Fukumoto et al first describing de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…Several reports showed that LIPUS repairs damaged peripheral nerve [31], accelerates healing of fractures [32, 33] and enhances angiogenesis [34, 35]. A recent report showed that LIPUS significantly enhances endothelial proliferation and induces angiogenesis [34].…”
Section: Discussionmentioning
confidence: 99%
“…Several reports showed that LIPUS repairs damaged peripheral nerve [31], accelerates healing of fractures [32, 33] and enhances angiogenesis [34, 35]. A recent report showed that LIPUS significantly enhances endothelial proliferation and induces angiogenesis [34].…”
Section: Discussionmentioning
confidence: 99%
“…Therapeutic pressure waves are often used to treat various musculoskeletal disorders as they are assumed to have thermal and mechanical effects on the target tissue resulting in an increased local metabolism and microcirculation, decreased pain and muscle tension, inhibition of muscle spasms, and accelerated healing [1,9,10,11,16,19,27]. At present, with the development and availability of precise research techniques in medicine, the assessment of possible therapeutic effect of physical therapy treatments including their dosage should be based on the objective findings of examination, supplemented by the evaluation of patient's medical condition and his/her subjective feelings.…”
Section: Discussionmentioning
confidence: 99%
“…According to our hypothesis, the heat generated during the treatment induces a reaction in the form of vasodilation and improvement of microcirculation, which increases the supply of oxygen to tissues, which -with simultaneous temperature rise and metabolism improvement -promotes its utilisation. According to the literature evidence, thermal and mechanical effects on the target tissue result in an increased local metabolism and microcirculation, promote re-perfusion and angiogenesis, reduce pain and muscle tension, inhibit muscle spasms, and accelerate healing [16,27,43]. Some researchers believe that these changes could account for the improved tissue repair which allegedly follows ultrasound therapy [44].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations